1986
DOI: 10.1007/bf01531727
|View full text |Cite
|
Sign up to set email alerts
|

Handedness patterns in autism suggest subtypes

Abstract: The present study reports preliminary data from two unselected samples of carefully diagnosed autistic subjects (children and adults) and an assessment procedure that includes a large sample of items, appropriate for lower-functioning autistic subjects, with multiple presentations within and between sessions 1 week apart. The study seeks to determine (1) whether a raised incidence of non-right-handedness exists in these samples (2) if so, what constructs best represent this shift in the handedness distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 24 publications
7
63
0
1
Order By: Relevance
“…This prediction held true even after controlling for parental handedness and postnatal maternal anxiety (odds ratio = 1.23, p < 0.05). These results complement findings of more mixed handedness in AD (Soper et al, 1986).…”
Section: Prenatal Stress Can Cause Behaviors Similar To Key Symptoms supporting
confidence: 61%
“…This prediction held true even after controlling for parental handedness and postnatal maternal anxiety (odds ratio = 1.23, p < 0.05). These results complement findings of more mixed handedness in AD (Soper et al, 1986).…”
Section: Prenatal Stress Can Cause Behaviors Similar To Key Symptoms supporting
confidence: 61%
“…[27][28][29][30]. However, other studies involving children, suggests that stronger hand dominance (left or right) correlates with both earlier language acquisition [31] and the successful hemispheric specialization for language [1].…”
Section: Introductionmentioning
confidence: 95%
“…However, studies which have used laterality judgements in autism have not necessarily found group differences (David et al, 2010). Previous studies into handedness in ASD have shown that many people with ASD are ambidextrous and may show an ambiguous handedness profile switching arbitrarily between left and right (Cornish and McManus 1996;Soper et al 1986). This could make it more difficult for them to make judgements about laterality due to confusion between left and right.…”
Section: Egocentric Transformations Taskmentioning
confidence: 99%